BIOSTIMULATIVE EFFECTS OF WATER HYACINTH (EICHHORNIA CRASSIPES (MART.) SOLMS) MULCH ON THE GERMINATION OF OKRA (ABELMOCHUS ESCULENTUS (L.)MOENCH) GROWN IN A CRUDE OIL CONTAMINATED SOIL - U.S. Offor; A.G. Iyagba; J. Onwugbuta-Enyi (European Scientific Journal, ESJ, 2013)
A field trial was carried out at the Teaching and Research Farm of the Ignatius Ajuru University of Education, Ndele campus near Port Harcourt, Nigeria to determine the effect of water hyacinth (Eichhornia crassipes (Mart.) Solms) mulch as biostimulant in a crude oil polluted soil using okra (Abelmochus esculentus (L.) Moench) as a test crop. The experimental treatments consisted of okra planted in a crude oil polluted soil, okra planted in a crude oil polluted soil amended with water hyacinth mulch (15 tons ha-1)and okra planted alone as the control. The land was polluted with crude oil at the rate of 6l m-2 of land. The treatments were laid out in a randomized complete block design and replicated four times. Okra plants grown in the crude oil polluted soil amended with water hyacinth mulch significantly enhanced okra seed germination at 4, 8 and 12 days after planting (DAP) and produced taller plants and more leaves than the control. Soil amended with water hyacinth mulch showed 6.6, 25.3 and 48.7% increase in seed germination at 4, 8 and 12 DAP respectively over the control. Water hyacinth mulch can therefore be used for the bioremediation of oil contaminated soil for okra cultivation.